Mechanical and fracture properties of bamboo - Low, , IM; Che, , ZY; Latella, , BA; Sim, , KS (2006)
The microstructure, mechanical, impact and fracture properties of Australian bamboo have been investigated. The graded composition and property has been confirmed by depth-profiles obtained by synchrotron radiation diffraction and Vickers indentation. The mechanical performance of bamboo is stronly dependent on age. Results showed that young bamboo has higher strength, elastic stiffness and fracture toughness than its old counterpart. Both crack-deflection and crack-bridging are the major energy dissipative processes for imparting a high toughness in bamboo.